Pengaruh Pembelajaran Online Di Era Covid 19 Terhadap Kesehatan Mental Mahasiswa - Mardiana Diana Mardiana; Alfian Mas’ud; Megawati Sibulo; A. Sri Ulfi Nofrianti; Irawati Irawati (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2022)
Introduction: Mental health is a state where an individual is free from all kinds of symptoms of mental disorders. An excellent mental condition occurs when the human mental illness is in a calm state. Individuals who have a healthy mental condition can carry their lives usually, especially when adjusting to face problems encountered throughout their lives, by using stress processing abilities. Mental health is an important thing that must be considered as physical health. Mental health conditions cannot be separated from good physical health conditions. Objective: This literature study aims to determine the effect of online learning in the covid-19 pandemic on the mental health of new students. Methods: The databases for this literature review are Plos One and Google Scholar. This article was taken in the 2020-2021 period with the provision of the language used for keywords, namely Indonesian and English, published nationally and internationally, and articles reviewed according to the topic being discussed. Results: The results that have been identified are as many as 104 articles, with the number of outcomes including as many as five articles. Conclusion: The effects of research from several articles in this literature review show that online learning is very influential on the mental health of new students because there are still many problems with online education in the covid-19 pandemic